Design and Characterization of Fatty Acid-Based Amino Acid Ester as a New "green" Hydrophobic Ionic Liquid for Drug Delivery - Md Moshikur, R. (American Chemical Society, 2020)
Ionic liquid (IL)-based drug delivery systems have attracted considerable interest owing to their intrinsic tunability and ability to transport small or large molecules through the skin. However, the development of "green"ILs remains challenging. Herein, eight potentially "green"fatty acid-based amino acid ILs (FAAAE-ILs) were synthesized, and their potency in transdermal drug delivery was investigated using ibuprofen and a peptide drug. The synthesized ILs were characterized to evaluate their physicochemical, thermal, and biological (cytotoxicity) properties. The in vitro skin permeability of the synthesized FAAAE-ILs was evaluated through pig skin. All of the FAAAE-ILs are liquid at room temperature and freely miscible with pharmaceuticals-permitted solvents/agents (e.g., isopropyl myristate (IPM), Span-20, and DMSO). In vitro cytotoxicity study showed that the cell viability of all FAAAE-ILs (10 in IPM) was at least 10 times lower than that for a conventional chemical permeation enhancer (CPE), sodium lauryl sulfate. FAAAE-ILs facilitated excellent ibuprofen solubility through multiple hydrogen bonding interactions between the drug and the ILs. An in vitro permeation study showed that the FAAAE-ILs were more effective in enhancing the permeability of drug molecules than the conventional CPE transcutol. The linoleate-based ILs showed a higher degree of permeation than the oleate-based ILs. Among the linoleate-based ILs and ibuprofen formulations (drug in 10 IL in IPM), the l-proline ethyl ester linoleate (l-ProEtLin)-based formulation exhibited best results, followed by Î²-alanine ethyl ester linoleate, d-proline ethyl ester linoleate, and l-leucine ethyl ester linoleate after 48 h. Interestingly, the same FAAAE-IL (l-ProEtLin)-containing formulation showed significant enhancement of peptide penetration across pig skin compared with CPE-containing formulations (10% in IPM). The results demonstrate that the FAAAE-IL is a promising green alternative to conventional CPEs for the transdermal delivery of small and large therapeutic molecules. Copyright Â© 2020 American Chemical Society.